Implementasi Aplikasi Penjualan Berbasis Customer Relationship Management untuk meningkatkan loyalitas pelanggan (Studi Kasus : T.B Gaya Baru) - Ayu Kartika Puspa (EXPERT: Jurnal Manajemen Sistem Informasi dan Teknologi, 2013)
The retail and shopping center showed significant growth and positive contribution to Indonesia's economic recovery. Intense competition makes it difficult for marketers to compete in product innovation. The development of increasingly rapid technological lead new thing will easily be able to be replicated by others, so the role of customer service is important. Customers who are satisfied with the service of the company on an ongoing basis will lead to customer loyalty. CRM (Customer Relationship Management) is a strategy used to get customers (acquire), strengthen relationships with customers (enhance) and retain customers (retain), and services aimed at improving customer satisfaction, operational, analytical, collaborative constitute components CRM.